Nostalgia narratives? Pejorative attitudes to welfare in historical perspective: survey evidence from Beveridge to the British Social Attitudes Survey. (26th October 2016) - Hudson, John; Lunt, Neil; Hamilton, Charlotte; Mackinder, Sophie; Swift, Chelsea; Meers, Jed
Abstract : Jensen and Tyler (2015) have powerfully argued that 'anti-welfare commonsense', fuelled by negative political and media discourse stressing welfare dependency and deception, has buttressed support for social security reform in recent years. Along with many other academics they point to the hardening of public attitudes towards welfare state provision and how notions of the 'deserving' and 'undeserving poor' have been reintroduced into popular debates. We identify four distinct threads within this scholarship. First, there is an argument that public attitudes have shifted from an earlier post-war welfare imaginary and settlement to an anti-welfare consensus. Second, this hardening includes a growing prevalence of 'othering'. The third thread is the broadening of this moral and disciplinary gaze to include groups, such as disabled people, who until recently were not subject to the same amount of stigma as other types of benefit recipients. Fourth, is the impact of pejorative welfare discourses on the self-identity and attitudes of disadvantaged groups. While a growing body of evidence makes it increasingly difficult to argue against suggestions that there is a hostile body of anti-welfare sentiment in the UK, what is often implicit in the analysis of pejorative contemporary attitudes to welfare is the view that there was once a 'golden age' of the welfare state when public support was more fully behind a strong set of social security benefits provided as a social right of citizenship. Whether this was the case is a moot point however. Few studies have tried to piece together the attitudes to welfare of the general public during the consensus era. We attempt to undertake such a task here, drawing on ad hoc attitudes surveys and polling data in particular. Specifically, we focus on how notions of the 'deserving' and 'undeserving poor' play out in this data, pointing to some key continuities found in contemporary and historical public attitudes to welfare.